Literasi Digital Siswa SMP di Jember sebagai Indikator Kesiapan dalam Menghadapi Era Masyarakat 5.0 dalam Pembelajaran IPA - Shelfy Rahma Andi Sofian; Wachju Subchan; Yushardi Yushardi (Postgraduate, University of Mataram, 2023)
In order to support educational needs, it is necessary to analyze student readiness in facing the era of society 5.0 by analyzing digital literacy. Digital literacy is a capability that needs to be analyzed before implementing digital technology-integrated learning.Â Science is a subject of learning that is closely related to the development of science and technology and need to be urged for its development in the society 5.0 era. This study uses a descriptive quantitative research method. The subjects in this study consisted of 75 junior high school students from two schools in Jember Regency who were selected by purposive sampling. The results of the study show that 4 aspects of digital literacy, namely functional skills, effective communication, critical thinking and evaluation, and e-safety are at an advanced level. While aspects of the ability to find and select information and aspects of cultural and social understanding are at the intermediate level. Another aspect that is at the basic level is creativity and collaboration. Referring to these results, students' digital literacy in Jember Regency is already good in various aspects, although there are some aspects that still need to be improved. Digital literacy has the opportunity to facilitate the learning process in the classroom in the era of society 5.0.